Enhanced piezoelectric properties and thermal stability in Mo/Cr co-doped CaBi2Nb2O9 high-temperature piezoelectric ceramics. (January 2020) - Chen, Zhenning; Zhang, Yuhao; Huang, Peiming; Li, Xudong; Du, Juan; Bai, Wangfeng; Li, Lili; Wen, Fei; Zheng, Peng; Wu, Wei; Zheng, Liang; Zhang, Yang
Abstract: Mo/Cr modified CaBi2 Nb2- x (Mo2/3 Cr1/3 ) x O9 ( x = 0.03, 0.04, 0.05, 0.06, 0.07, 0.075, and 0.1) were synthesized by the conventional solid-state reaction method. The effects of Mo/Cr substitution for Nb on structure, dielectric properties, piezoelectric properties and electrical conduction behaviours of CBN were investigated in detail. Results showed that moderate substitution of Nb with Mo/Cr optimized crystal structure and led to a reduction in oxygen vacancies, which effectively improved the electrical properties of the CBN ceramics. The CaBi2 Nb1.93 (Mo2/3 Cr1/3 )0.07 O9 ceramic showed optimal properties with a high d 33 of 15 pC/N along with a high T C of 939 °C, an enhanced electrical resistivity ( ρ ) of 3.33 × 10 5 Ω cm accompanied by a decreased dielectric loss of tanδ = 6.5% at 600 °C. Furthermore, the ceramic also exhibited a remarkable thermal stability performance that d 33 remained 93% of its original value when the annealing temperature rose up to 850 °C. All these properties demonstrated the great potentials of Mo/Cr doped CBN-based ceramic for high-temperature applications. Highlights: Mixed-valence cations Mo 6+ /Cr 3+ modified CaBi2 Nb2 O9 piezoceramics were synthesized. Large d 33 value of 15 pC/N together with a high T C of 939 °C was achieved. Excellent thermal stability and enhanced electrical resistivity were obtained.